INCIDENTAL FOCUS ON FORM, NOTICING AND VOCABULARY LEARNING IN THE EFL CLASSROOM - Alcón, Eva (International Journal of English Studies, 2009)
This study examines the effectiveness of teachers’ incidental focus on form on vocabulary learning. Seventeen 45-minute audio-recorded teacher-led conversation, 204 learners’ diaries (17 sessions x 12 learners) reporting what the participants had learned after each conversational class, 204 post-test translations, and 204 delayed post-test translations, which were created on the basis of the items reported in learners’ diaries were used to trace teacher involvement in pre-emptive and reactive lexically-oriented focus on form episodes (FFEs) to vocabulary learning. The results revealed that teachers’ pre-emptive FFEs are effective for learners’ noticing and subsequent use of vocabulary items. On the other hand, teacher reactive FFEs do not seem to facilitate noticing, as measured by learners’ reporting of vocabulary items, but they do facilitate vocabulary learning, as measured by subsequent use of vocabulary items in the post-test and delayed post- tests. These results suggest that incidental focus on form might be beneficial for learners, and further research issues on incidental focus on form are suggested.